2016
DOI: 10.31299/hrri.52.1.4
|View full text |Cite
|
Sign up to set email alerts
|

Audiometric Findings in Patients with Subjective Tinnitus

Abstract: Tinitus je percepcija zvuka u odsutnosti vanjskog izvora zvuka. U većini slučajeva tinitus je prisutan uz istovremeno oštećenje sluha. Cilj istraživanja bio je utvrditi učestalost, vrstu i stupanj oštećenja sluha u pacijenata sa subjektivnim tinitusom te analizirati karakteristike tinitusa u odnosu na oštećenje sluha. Analizirali smo audiometrijske, otoskopske nalaze i medicinske izvještaje 1046 pacijenata, 573 muškaraca (54.8%) i 473 žena (45.2%), u dobi od 19 do 89 godina. Pacijenti su pregledani na Odjelu z… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
1
1
0
Order By: Relevance
“…In present study high-pitch whistling was predominant in patients with tonal tinnitus. It was also reported in a previous studies (Ristovska et al, 2016;Crummer, Hassan, 2004;Martines et al, 2010).…”
Section: Discussionsupporting
confidence: 84%
“…In present study high-pitch whistling was predominant in patients with tonal tinnitus. It was also reported in a previous studies (Ristovska et al, 2016;Crummer, Hassan, 2004;Martines et al, 2010).…”
Section: Discussionsupporting
confidence: 84%
“…(2002) also found associated hearing loss of known ethology in almost 90% of tinnitus patients. A more recent study has shown that 91.9% of tinnitus patients had hearing loss at conventional audiometric test frequencies, 125-8000 Hz (Ristovska et al, 2016). In tinnitus patients with normal hearing in conventional audiometry tinnitus may be explained by an extended high frequency (EHF) hearing loss (Rodriguez Valiente et al, 2016).…”
Section: Introductionmentioning
confidence: 99%